Physical characterization of the main trails in the Alberto Manuel Brenes Biological Reserve - Moya Calderón, Michael Mauricio (2017)
Through the application of the geographic information systems (GIS), the topographic profiles and slope-accessibility maps of seven paths at Alberto Manuel Brenes Biological Reserve were created. The base input were the line trails and the sheet level curves obtained by using San Lorenzo (10m), this data was used to elaborate a Digital elevation model (MED), used for the later design of the profiles and the slope maps. The obtained results are more than a mere physical description of the trails, they englobe a source of information for the management of protected areas, since they provide valuable information  about sections with higher degradation probability for both researchers  and those who are in charge of trail section